HER2-Specific T Lymphocytes Kill both Trastuzumab-Resistant and Trastuzumab-Sensitive Breast Cell Lines In Vitro - Lin, Xiao-lin; Wang, Xiao-li; Ma, Bo; Jia, Jun; Yan, Ying; Di, Li-jun; Yuan, Yan-hua; Wan, Feng-ling; Lu, Yuan-li; Liang, Xu; Shen, Tao; Ren, Jun (Chinese Journal of Cancer Research; Vol 24, No 2 (June 29, 2012): Chinese of Journal Cancer Research, 2012)
Objective: Although the development of trastuzumab has improved the outlook for women with human epidermal growth factor receptor 2 (HER2)-positive breast cancer, the resistance to anti-HER2 therapy is a growing clinical dilemma. We aim to determine whether HER2-specific T cells generated from dendritic cells (DCs) modified with HER2 gene could effectively kill the HER2-positive breast cancer cells, especially the trastuzumab-resistant cells. Methods: The peripheral blood mononuclear cells (PBMCs) from healthy donors, whose HLA haplotypes were compatible with the tumor cell lines, were transfected with reconstructive human adeno-association virus (rhAAV/HER2) to obtain the specific killing activities of T cells, and were evaluated by lactate dehydrogenase (LDH) releasing assay. Results: Trastuzumab produced a significant inhibiting effect on SK-BR-3, the IC50 was 100ng /ml. MDA-MB-453 was resistant to trastuzumab even at a concentration of 10,000 ng/ml in vitro. HER2-specific T lymphocytes killed effectively SK-BR-3 [(69.86±13.41)%] and MDA-MB-453 [(78.36±10.68)%] at 40:1 (effector:target ratio, E:T), but had no significant cytotoxicity against HER2-negative breast cancer cell lines MDA-MB-231 or MCF-7 (less than 10%). Conclusion: The study showed that HER2-specific T lymphocytes generated from DCs modified by rhAAV/HER2 could kill HER2-positive breast cancer cell lines in a HER2-dependent manner, and result in significantly high inhibition rates on the intrinsic trastuzumab-resistant cell line MDA-MB-453 and the tastuzumab-sensitive cell line SK-BR-3. These results imply that this immunotherapy might be a potential treatment to HER2-positive breast cancer.